Isolation of a selenium-containing thiolase from Clostridium kluyveri: identification of the selenium moiety as selenomethionine. - Hartmanis, M G (1982)
Clostridium kluyveri grown in the presence of 1 muM Na2(75)SeO3 produces a thiolase that copurifies with 75Se. Based on several criteria, the selenium moiety in this protein is selenomethionine. The 75Se-labeled amino acid in acid hydrolysates of the radioactive protein cochromatographed with authentic selenomethionine on an amino acid analyzer and on TLC plates in acidic and basic solvents. Incubation with S-adenosylmethionine synthetase and ATP converted the 75Se-labeled amino acid to a radioactive basic product that was indistinguishable from authentic Se-adenosylselenomethionine by ion exchange and TLC. The native selenoenzyme, Mr 155,000-158,000, is composed of four subunits of Mr 38,000-40,000. Thiolase of similar molecular weight that is less acidic and lacks selenium is also produced by C. kluyveri. The factors that control the relative levels of the two enzymes in the cell have not been identified.